Upaya Penguatan Sikap Nasionalisme Siswa SDN 1 Penjor Melalui Habituasi Menyanyikan Lagu Kebangsaan - Ardila Nada Nuritama; Andreas Andrie Djatmiko (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of the habituation of singing the national anthem in strengthening students' nationalism at SDN 1 Penjor and identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of teachers and students of SDN 1 Penjor. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while data validity was tested using source and technique triangulation. The results of the study indicate that the habituation of singing the national anthem before learning can strengthen students' nationalism, which is reflected in an increase in love for the homeland, discipline, responsibility, respect for state symbols and ethics, and a growing sense of togetherness and unity among students. Supporting factors for the implementation of the activity include school support, cooperation between teachers, a conducive school environment, availability of facilities, and student enthusiasm. Inhibiting factors include weather conditions, internet network disruptions, lack of concentration among some students, and the continued lack of confidence in singing the national anthem.